Cultural depictions of the European fallow deer (Dama dama) 6000 BCE to 1600 CE - Ward, Christopher (2017)
This thesis will seek to illustrate the social and cultural role which the European Fallow Deer has played in the period 6000 BCE – 1600 CE by investigating cultural depictions of the animal. These cultural depictions take various forms, in material culture, iconography and literary works as well as in its conceptions and classifications. Taking specific examples of practices throughout the eras, each will be examined in regard to the historical, cultural and ecological contexts and the fallow deer itself. Although many depictions, especially from earlier eras would appear scant, and later depictions are very geographically and culturally specific, the perception of the deer by cultures is a worthwhile and meaningful exploration. This present work gives particular attention to the ancient Greeks, the Thracians, the Romans, and the medieval British, who all appeared to invest heavily in the species and in its cultural depictions and movements. Depiction of fallow deer will be discussed from the Neolithic period, through the medieval until the 17th century at around the time the medieval emparkment and sovereignty systems ended. Whilst fallow deer has become a staple for the many deer parks of Europe, and has been introduced across the world, historical research into the human approaches and efforts shown towards the animal by species and classifications has been minimal. As part of an AHRC funded project, this species of deer has been subject to intensive study. It is hoped that this research will complement the project’s work and that a better understanding of the human perception and efforts regarding the animal may be attained.